Penggunaan Pendekatan Saintifik Melalui Aktivitas Window Shoping untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VIIIC SMPN 13 Mataram - Erna Ekawati (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
The purpose of this class action research (CAR) is to find out: 1) the use of a scientific approach through window shopping activities to improve the learning outcomes of class IIC students at SMPN 13 Mataram. 2). The Effectiveness of the Scientific Approach through window-shopping Activities to improve the learning outcomes of Class IIC students at SMPN 13 Mataram This action research was conducted in 3 cycles. From the results of the actions taken, it is proven to be able to improve student learning outcomes by achieving ideal standards. From 58.15% in Cycle I, it can increase in Cycle 2 to 73.24% and in Cycle 3 to 88.87%, and classically it has achieved completeness. The results of this action research show that learning using a scientific approach through Windows shopping activities can improve the abilities and learning activities of class VIII-C students with completeness reaching 100%, thus the use of a scientific approach through Windows shopping activities is effective in improving student learning outcomes at SMP Negeri 13 Mataram.